A Systems Approach to Remediating Human Exposure to Arsenic and Fluoride From Overexploited Aquifers. (2nd July 2022) - Knappett, P. S. K.; Farias, P.; Miller, G. R.; Hoogesteger, J.; Li, Y.; Mendoza‐Sanchez, I.; Woodward, R. T.; Hernandez, H.; Loza‐Aguirre, I.; Datta, S.; Huang, Y.; Carrillo, G.; et al.
Abstract: In semiarid agricultural regions, aquifers have watered widespread economic development. Falling water tables, however, drive up energy costs and can make the water toxic for human consumption. The study area is located in central Mexico, where arsenic and fluoride are widely present at toxic concentrations in well water. We simulated the holistic outcomes from three pumping scenarios over 100 years (2020–2120); (S1) pumping rates increase at a similar rate to the past 40 years, (S2) remain constant, or (S3) decrease. Under scenario S1, by 2120, the depth to water table increased to 426 m and energy consumption for irrigation increased to 4 × 10 9 kWh/yr. Arsenic and fluoride concentrations increased from 14 to 46 μg/L and 1.0 to 3.6 mg/L, respectively. The combined estimated IQ point decrements from drinking untreated well water lowered expected incomes in 2120 by 27% compared to what they would be with negligible exposure levels. We calculated the 100‐year Net Present Value (NPV) of each scenario assuming the 2020 average crop value to water footprint ratio of 0.12 USD/m 3 . Without drinking water mitigation, S1 and S3 yielded relative NPVs of −5.96 × 10 9 and 1.51 × 10 9 USD, respectively, compared to the base case (S2). The relative NPV of providing blanket reverse osmosis treatment, while keeping pumping constant (S2), was 11.55 × 10 9 USD and this gain increased when combined with decreased pumping (S3). If a high value, low water footprint crop was substituted (broccoli, 1.51 USD/m 3 ), the net gains from increasing pumping were similar in size to those of implementing blanket drinking water treatment. Plain Language Summary: Groundwater is jointly used by for‐profit agriculture and domestic households for drinking water. Although agriculture creates jobs and stimulates investment, preventing the exposure of children to neurotoxins in drinking water generally means a more prosperous future. We calculate falling water tables, rising energy costs, increasing concentrations of naturally occurring neurotoxins, decreasing IQ and earnings for people living in the basin owing to different rates of pumping by agriculture. For the different pumping scenarios, we calculate the increase or decrease in revenue for the agriculture sector. We then calculate the net economic gain from increasing or decreasing pumping rates, growing alternative crops, and treating drinking water to remove the neurotoxins. We found that people's personal incomes will be ever‐more reduced by their exposure to higher concentrations of neurotoxins. The benefits of treating water to remove the neurotoxins are much greater than the costs. Furthermore, increasing pumping rates is only profitable over the long term if it is accompanied by growing much higher value and lower water demand crops than are currently being irrigated in the study area. The most urgent issue, at least from an economic growth perspective, is not limiting pumping but rather treating the drinking water. Key Points: Overexploiting aquifers increases energy costs and lowers economic productivity by increasing human exposure to geogenic neurotoxins Over a 100 year future time‐frame estimated revenue from agro‐export will be less than the costs this activity imposes on the population Investing in water treatment substantially lowers costs of deteriorating water quality